The background of slapstick in Menander’s comedy: throwing objects, hitting, tripping, and comic falls (2021)
Greek literature has a background of slapstick resources (hits, falls, stumbling, throwing objects, and comic injuries) in various genres such as epic, iambic poetry, fable, and comedy. Menander’s comedy, in particular The Misanthrope, makes extensive use of this series of topics of physical humor to characterize the old man Knemon, his central character. In some of his works, slapstick is specifically associated with the -typical grumpy old man character. The Misanthrope clearly takes up the  traditional punitive use of the resource, which is dominant in Aristophanes’ comedy, insofar as slapstick aims to punish and transform Knemon’s antisocial behavior. It is not a resource associated with mere entertainment, but it condemns either its victim through the derision of aggression and laughter or its victimizer, when he exerts decontextualized violence, as does the misanthrope.